간호대학생의 체형만족도와 비만스트레스가 진로준비행동에 미치는 영향 - 정향진; Hyang-jin Jeong (의료커뮤니케이션, 2019)
Purpose: This descriptive research study was effect of satisfaction of body figure and obesity stress on career preparation behavior in nursing college students. Survey design was adopted for 210 nursing college students in Gyeong Sang Buk Do. Methods: Data were gathered from May 1 to May 31, 2019 Analysed for descriptive statistics, independent t-test, ANOVA, Pearson correlation, and hierachical multiple regression analysis. Results: There was a significant negative correlation between satisfaction of body figure and obesity stress, and was a positive correlation between career preparation behavior and obesity stress. Factors affecting career preparation behavior in the subjects were grade, subjective body shape, motivation for entering college, and stress from weight control efforts. This model explained 16% in career preparation behavior. Conclusion: The results suggest that an intervention program is needed to improve career preparation behavior, to teach the right knowledge about body shape and to emphasize the importance of health care in the nursing college students.